2009
DOI: 10.1111/j.1463-1318.2008.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging accuracy in assessing tumour down‐staging following chemoradiation in rectal cancer

Abstract: Objective Magnetic resonance imaging (MRI) is increasingly accepted as the radiological modality of choice staging rectal cancer but is subject to error. Neoadjuvant therapy is increasingly used in rectal cancer and MRI is used to stage response and occasionally plan surgery. We aim to assess the staging accuracy of MRI following chemoradiotherapy in rectal cancer.Method Retrospective analysis of 86 patients with MRI stage pre-and postlong-course chemoradiotherapy and comparison with pathological assessment.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 16 publications
2
46
0
2
Order By: Relevance
“…These findings also may have affected oncologic outcomes. Although the MERCURY group believes that MRI after nCRT should be mandatory and is very helpful in predicting pathologic T stage and prognosis [7], others argue that MR reimaging after nCRT is of limited value because of its low accuracy [25,26,27]. The MERRION study, in particular, showed that the positive predictive value [18.2% (2/11)] and κ statistics (0.021) of MRI were very poor in predicting pathologic CR [25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings also may have affected oncologic outcomes. Although the MERCURY group believes that MRI after nCRT should be mandatory and is very helpful in predicting pathologic T stage and prognosis [7], others argue that MR reimaging after nCRT is of limited value because of its low accuracy [25,26,27]. The MERRION study, in particular, showed that the positive predictive value [18.2% (2/11)] and κ statistics (0.021) of MRI were very poor in predicting pathologic CR [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proved that ERUS is still the most accurate method to determine neoplastic wall infiltration and lymph node involvement even after RCT [78,79] . After neoadjuvant treatment, the status of the lymph nodes remains a problem; ERUS and MRI both have a low accuracy to evaluate metastatic lymph nodes after neoadjuvant [80] . For the correctly restaging rectal cancer after neoadjuvant treatment, it is of vital important to choose the correct time between the end of neoadjuvant therapy and the procedure of ERUS.…”
Section: Other Rectal Massesmentioning
confidence: 99%
“…The TRG score accurately reflects the variation in the biological response to radiation, also in the absence of T stage change [25]. The common methods for monitoring the tumor response to neoadjuvant CRT, such as physical examination and conventional imaging modalities, have several limitations due to the difficulties in the distinction between disease persistence and treatment-induced fibrosis [9]. Up to 75% of patients who appear to have obtained a clinical complete response still have microscopic disease at the time of full thickness biopsy [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of downstaging or pathological complete response (pCR) after neoadjuvant CRT is correlated with improved survival, decreased local recurrence, and higher chances of sphincter-preserving surgeries [4,5,6,7]. Conventional imaging modalities, including CT, MRI, and endoscopic ultrasound, have shown promise in monitoring the response to neoadjuvant CRT [8,9,10]. However, these techniques rely on the documentation of morphological changes, with limited accuracy and reproducibility in determining clinical downstaging and distinguishing viable tumor from fibrotic tissue.…”
Section: Introductionmentioning
confidence: 99%